Oxidant-antioxidant status in tissue samples of oral leukoplakia - Kumar Chandan Srivastava; Ravi David Austin; Deepti Shrivastava; Gopalakrishnan Pranavadhyani (Wolters Kluwer Medknow Publications, 2014)
Background: Imbalances between the oxidant-antioxidant status have been implicated in the pathogenesis of several diseases, including oral cancer. Majority of oral cancer are preceded by a well-recognized group of pre-malignant lesions. However, only a small fraction of those lesions, undergo malignant transformation. Hence, there is a great need to identify biological markers, which will assist in identifying lesion carrying high-risk. This study aims to evaluate and compare the status of oxidative stress and antioxidant enzymes in tissue samples of patients with various clinicopathological stages of oral pre-malignancy. Materials and Methods: A case control study consisting of 20 new histopathologically proven leukoplakia patients and equal number of age, sex, and habit matched healthy subjects were recruited for this study. Their tissue samples were subjected to evaluation of lipid peroxidation product, thiobarbituric acid reactive substances and antioxidant enzymes, namely, superoxide dismutase (SOD), catalase (CAT), reduced glutathione (GSH), and glutathione peroxidase (GPx) using spectrophotometric methods. The data are expressed as mean ± standard deviation. The statistical comparisons were performed by independent Student's unpaired t-test and one-way analysis of variance. Pearson's correlation was performed for the biochemical parameters within the group and between the groups. For statistically significant correlations, simple linear regression was performed. P- value < 0.05 was considered statistically significant. Results: Significant reduction in lipid peroxidation (P < 0.001) SOD and CAT (P < 0.001) was observed in the tissue of leukoplakia patients as compared to the healthy controls. On the other hand, GSH and GPx were significantly increased in tumor samples. Conclusion: Reduced lipid peroxidation and increased activity of GSH and GPx provides the suitable environment for the tumor growth and malignant transformation in the later stages. Among the antioxidant enzymes, glutathione reductase appears to have a profound role in carcinogenesis.